The adsorption of CO on potassium doped molybdenum carbide surface: An ab-initio study - Pistonesi, Carolina (2012)
We have studied the effect of K on the adsorption of CO on the β-Mo 2C (0 0 1) surface with a periodic supercell method using Density Functional Theory calculations, with the PBE functional the generalized gradient approximation. The most favorable sites for CO adsorption are three-fold carbon deficient Mo sites on both clean and K promoted surface. Adsorption is more favorable in the presence of K. The electronic configuration analysis shows that in all cases the CO molecule withdraws charge from the surface, the larger charge transfer occurs on the K promoted surface.